MESOZOIC SPREADING KINEMATICS: CONSEQUENCES FOR CENOZOIC CENTRAL AND WESTERN MEDITERRANEAN SUBDUCTION - Capitanio F.A.; Goes S. (My University, 2006)
The highly complex tectonics of Central and Western Mediterranean subduction are well documented, but there is significant debate about the responsible dynamics. The motions of the main plates, Africa including Adria, Europe and Iberia, imposed initial and boundary conditions on the evolution of subduction that are often not considered. To quantitatively evaluate these conditions, we make a set of reconstructions from Mesozoic opening through Cenozoic closing of the Alpine Tethys, using main-plate kinematic data from several authors. Geologic and tectonic information are only added to constrain the location of the break-up boundary and a single plate-margin rearrangement at the end of the opening phase. Otherwise, the plates remain undeformed. This rigid-plate approach illustrates the context in which surface deformation and subduction occurred and provides estimates (with uncertainties) of the amount of material that should be accounted for in orogens or documented seismically in the mantle. Full tectonic reconstructions should satisfy such constraints. Opening led to alternating domains of predominantly oceanic lithosphere formed by normal spreading and domains dominated by transform motion, floored mainly by extended continental lithosphere. The transform domain structures provide logical decoupling zones to allow Penninic, Ligurian and Pyrenean basins to start subducting independently. The complex buoyancy in the transform domain linking Ligurian and Penninic basins, and obliquity between directions of opening and closing may account for a number of the oceanic basins and continental slivers often invoked to explain Alpine geology. The significant proportion of continental lithosphere in the Alboran would have favoured delamination of mantle lithosphere over subduction. The almost completely subducted Penninic slab obstructed subduction of the Ligurian domain in the direction of Africa-Europe convergence, possibly forcing the rollback of the Appeninic/Calabrian trench. © 2006 The Authors Journal compilation © 2006 RAS.
Keywords: LITHOSPHERE; MEDITERRANEAN; PLATE MOTIONS; SUBDUCTION